Regorafenib-Induced Radiation Recall Presenting as Acute Blood Loss Anemia With Rectal Bleeding and Severe Proctitis - Madhulika Urella MD; Mina Shenouda MD; Toni Pacioles MD (SAGE Publishing, 2023)
Radiation recall is a rare inflammatory reaction that occurs in an area that was subjected to prior irradiation that is usually triggered by certain drugs or chemotherapy agents. This reaction is drug-specific for each individual and occurs in about 6% to 9% of the patients receiving chemotherapy after radiation therapy. We report a case of radiation recall-induced severe proctitis which is thought to be triggered by administration of regorafenib for stage IV rectal adenocarcinoma with lung metastases. We present a 65-year-old female patient who was initially diagnosed with stage III T4N1M0 rectal adenocarcinoma that was treated with neoadjuvant concurrent chemoradiotherapy, followed by low anterior resection. The tumor was pathologically staged a ypT3 yN1 with a partial response to the treatment. After the surgery, the patient was found to have lung nodules consistent with metastatic disease, when she was treated initially with folinic acid, fluorouracil, and oxaliplatin, plus bevacizumab. The patient had further disease progression with metastases in her lungs despite treatment with several chemotherapy agents. She was started on regorafenib, an oral vascular endothelial growth factor inhibitor, as a fourth line of therapy. However, in a month after initiation of oral regorafenib, and 9 months after the prior radiation treatment, the patient presented to the emergency room with a complaint of bright red blood per rectum. She was diagnosed with severe radiation proctitis that was treated therapeutically with argon plasma coagulation. This particular case serves as a reminder that although infrequent and rare, radiation recall may result in an inflammatory reaction in an organ such as rectum. To the best of our knowledge, this regorafenib-induced severe proctitis secondary to radiation recall has not been reported in the literature before.